Efficacy of suction blister epidermal grafting with concomitant phototherapy in vitiligo treatment - Iwanowski, Tomasz; Szlązak, Piotr; Rustowska, Alicja; Sokołowska-Wojdyło, Małgorzata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : There are many surgical methods for vitiligo treatment that have been used for over 30 years. Suction blister epidermal grafting (SBEG) is considered one of the simplest and most effective of them. Aim : To determine how effective suction blister grafts with concomitant phototherapy are in vitiligo treatment. Material and methods : The study was conducted on 10 patients with vitiligo that was resistant to previous treatment including phototherapy in monotherapy. Involvement of affected sites was different for every patient. We used cryotherapy for blistering at the recipient site and an automatic suction device for blistering at the donor site. The blister was separated from the donor site and fixed with dressing to the recipient site. After removing the final dressing (about 7 days after SBEG) patients started phototherapy (6 patients had UVB 311 nm and 4 had PUVA). All patients treated with UVB 311 nm were qualified for treatment in our clinic and the method was chosen according to expert recommendations from the European Dermatology Forum (EDF) Guidelines for Vitiligo where narrowband (NB) UVB is the phototherapy of choice. Three patients who had PUVA therapy were treated with this method in other clinical centers and sent to us only to undergo SBEG. One patient had previously received UVB 311 nm for 3 months, which showed no effects. Repigmentation of lesions was evaluated at 3 and 6 months after the surgical procedure. Results : Ten patients (9 females with a mean age of 36.88 years and 1 man aged 39 years) were enrolled in the study. Nine patients showed progressive repigmentation at 3 and 6 months follow-up with a rate varying from 13 to 76% (mean: 44.5%) and 35 to 100% (mean: 67.5%). One patient showed 5% depigmentation at a visit after 6 months in comparison to the follow-up visit 3 months after SBEG. Conclusions : With this technique, patients who did not respond to the usual treatments showed very good repigmentation over a 6-month follow-up. There were no side effects such as scarring.